"I Just Don't Think There's any other Image that Tells the Story like [This] Picture Does": Researcher and Participant Reflections on the Use of Participant-Employed Photography in Social Research. Issue 1 (February 2014) - Burles, Meridith; Thomas, Roanne
The incorporation of visual forms of expression has become common in qualitative research over the past two decades, with participant-employed photography being most prevalent. Visual methods such as photovoice have been used in community-based studies and with individuals to explore their lived experiences, particularly because of their participatory nature. Despite widespread support for visual approaches in existing research, there has been insufficient attention paid to how photography can enhance understanding of the phenomenon under study. Additionally, the existing literature is somewhat bereft of discussion of what individuals think about their participation in studies that incorporate participant-employed photography, or researchers' perspectives of carrying out this type of research. In this article, we describe a photovoice study carried out with young adult women affected by serious illness and provide examples of participants' photographs to illustrate how participant-employed photography can enhance the depth of research data. Specifically, the examples highlight how the photographs enriched participants' verbal descriptions of their lived experiences, which generated a better understanding of their personal embodied realities. We also discuss the young adult women's inclusion of previously taken photographs and reflections on their participation in the study. Finally, we examine the need to consider the intended audience of photographs, and specific ethical and methodological considerations for researchers contemplating the incorporation of participant-employed photography. In doing so, we provide insight into the advantages and challenges of photo-methods, which can inform other researchers contemplating the incorporation of participant-employed photography into social research.